Reconceptualising the tudung: Malay women, social media and modern lifestyles / Fauziyah Hanim Abdul Ree, Md Azalanshah Md Syed and Azizah Hamzah. - Abdul Ree, Fauziyah Hanim; Md Syed, Md Azalanshah; Hamzah, Azizah (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2020)
This qualitative research examines the reconceptualisation of tudung as modern lifestyle among Malay women in contemporary Malaysia. With the emergence of social media, the image of tudung has been reinvented from mundane subject to be more colourful and stylish and emerge as modern popular culture in the Malay society. The popularity of tudung has created criticism among the religious authorities over the structured meaning of tudung as a symbol of female modesty. The reconceptualisation of tudung in this context refers to the tudung representation as Malay women engage with modernity. The process reflects the complex relationship as they negotiate within the existing traditional Malay structure and religious requirement.